Prevalence of child underweight, maternal malnutrition and pregnancy weight gain of urban poor of Dhaka and Chittagong, Bangladesh: an analysis of growth monitoring and promotion cards (Bangladesh Journal of Nutrition, 2018)
Child and maternal malnutrition is a major public health problem in Bangladesh. The study assessed children and pregnant women malnutrition, and pregnancy weight gain in urban poor areas of Dhaka and Chittagong City, Bangladesh. This longitudinal study analyzed data of children 4 kg) during the third trimester. Overall, 35.4% of pregnant women conducted 3 or more antenatal care visits throughout her pregnancy period. Prevalence of child and maternal malnutrition was significantly high in urban poor areas of Dhaka than those in Chittagong areas. Lack of continued participation in GMP program is a great challenge. Nutrition intervention programs should be intensified in the urban poor areas to address maternal and child nutrition problems.Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 73-80